Peran Masyarakat Dalam Meningkatkan Wisata Religi Makam Kyai Atas Angin Di Desa Maguwan, Kecamatan Sambit Kabupaten Ponorogo - Wicaksono, Wahyu Rimba (Journal of Community Development and Disaster Management, 2024)
Dakwah is an integral part of Islamic teachings that every Muslim is obliged to practice. This obligation is reflected in the concepts of amar ma'ruf and nahi munkar, any dakwah technique will lose its effectiveness and efficiency in realizing Islam in all dimensions without being based on a clear strategy. So that various strategies for delivering da'wah to modern society in Indonesia are very important, in addition to efforts to reconstruct da'wah strategies for the future. In the process of building there are also factors that influence the community to participate in an activity, these factors are the ability, and opportunities for the community to participate. Meanwhile, in Maguwan village, the condition that became a phenomenon was that after the author made initial observations at the location, it was known that visitors at the Kyai Atas Angin Tomb in Maguwan village who came at this time decreased. So the author is interested in assessing the decrease in the number of visitors who come to the religious tourism site of Maguwan village. The need for active support and participation from the local community, especially the wisdom of its citizens and the millennial generation who are active in welcoming the development of religious tourism in Maguwan village, as well as the innovation model of religious tourism destinations in Maguwan village. Dakwah merupakan bagian integral dari ajaran Islam yang wajib dilaksanakan oleh setiap muslim. Kewajiban ini tercermin dari konsep amar ma’ruf dan nahi munkar, Teknik dakwah apapun akan kehilangan efektivitas dan efesiensinya dalam merealisir Islam dalam semua dimensi tanpa berdasarkan dari strategi yang jelas. Sehingga berbagai strategi penyampaian dakwah bagi masyarakat modern di Indonesia menjadi hal yang sangat penting, disamping upaya rekonstruksi strategis dakwah bagi masa depan. Dalam proses pembangun terdapat pula faktor-faktor yang mempengaruhi masyarakat untuk turut berperan dalam suatu kegiatan, faktor tersebut adalah kemampuan, dan kesempatan bagi masyarakat untuk berpartisipasi . Sedangkang di desa Maguwan kondisi yang menjadi fenomena ialah setelah penulis melakukan observasi awal di lokasi tersebut diketahui bahwa pengunjung di Makam Kyai Atas Angin di desa Maguwan yang datang saat ini menurun. Sehingga penulis tertarik untuk mengakaji penurunan dari jumlah pengunjung yang datang di lokasi wisata religi desa Maguwan. Perlunya dukungan dan partisipasi aktif dari masyarakat lokal khususnya kearifan warganya serta giat generasi milenial dalam menyongsong perkembangan wisata religi di desa Maguwan, serta model inovasi destinasi wisata religi di desa Maguwan.